2017
DOI: 10.3390/nu9030231
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Manganese Levels with  Alzheimer’s Disease and Mild Cognitive Impairment:  A Systematic Review and Meta‐Analysis

Abstract: Manganese (Mn) is one of the most studied environmental heavy metals linked to Alzheimer’s disease (AD). However, it remains unclear whether serum Mn levels are associated with AD and mild cognition impairment (MCI, a prodromal stage of AD). We conducted a meta-analysis to analyze the serum Mn levels in patients with AD and MCI. A systematic database search of PubMed, Web of Science, and the China National Knowledge Infrastructure (CNKI) identified 17 studies, including 836 cases and 1254 health controls (HC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Similarly, manganese level analysis in the recent studies revealed controverted results. The most recent meta-analysis on the matter, Du et al [ 30 ], reports controversial dynamics of manganese levels presenting several studies which show a significant decrease of this parameter in demented patients' sera, while in other studies, no difference or significant increase were obtained. We also found statistical correlations between MMSE scores versus manganese levels and ADAS-COG versus magnesium and manganese levels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, manganese level analysis in the recent studies revealed controverted results. The most recent meta-analysis on the matter, Du et al [ 30 ], reports controversial dynamics of manganese levels presenting several studies which show a significant decrease of this parameter in demented patients' sera, while in other studies, no difference or significant increase were obtained. We also found statistical correlations between MMSE scores versus manganese levels and ADAS-COG versus magnesium and manganese levels (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Studies are consistent in reporting an increased deposition of manganese in the brain of patients suffering from hepatic encephalopathy (HE) [63,64,65,66,67,68,69]. This is depicted in the form of hyperintense MRI signals, in particular in the region of the brain called the globus pallidus [70].…”
Section: Manganese In Alcoholismmentioning
confidence: 96%
“…Compromised liver function does not allow for proper detoxification, and one of the results is a free passage of neurotoxins entering the brain. As increased amounts of manganese are deposited in the brain, and in particular in the astrocytes, this causes Alzheimer type II changes, as well as selective neuronal loss in the basal ganglia [66,67,68]. Similar effects are seen in ammonia deposition in the brain [69].…”
Section: Manganese In Alcoholismmentioning
confidence: 99%
“…Regarding the individual metals, more recent studies of aluminium report significantly increased mortality from AD among miners exposed to aluminium-rich dust [147] suggesting that some aspects of this hypothesis might be worth revisiting. In addition to aluminium [195], zinc [127,192], mercury [140], copper [86,144], manganese [45,186], cadmium [136,142], and magnesium [188] have all been suggested as risk factors for AD. Many of these metals have been shown to interact directly with APP metabolism or with APOE [140].…”
Section: Metalsmentioning
confidence: 99%